Edukasi Peningkatan Literasi Keuangan Bagi SMK Negeri 1 Musuk Agar Menjadi Generasi yang Cerdas Akan Financial - Agus Tri Mulyanto; Fatimah Shofia Bagaswati; Hilda Wulandari; Karisma Putri Nur A; Lio Bijumes (Lembaga Pengembangan Kinerja Dosen, 2026)
Financial literacy is a crucial competency for today’s young generation, especially Gen Z, who are currently in the midst of the development of financial technology. However, the level of financial literacy among vocational and high school students is still relatively low, including students at SMK Negeri 1 Musuk. This community service activity, which includes outreach activities, aims to provide and improve students’ understanding and also change students’ attitudes towards financial literacy so they can manage their finances well, wisely, and responsibly. The method used in this outreach activity is a qualitative method with a type of outreach activity consisting of several stages or sessions: the first is the observation session, the second is the activity planning, and the third is the implementation of the outreach activity. This activity was carried out on December 5, 2025, with 30 participants from class XI AKL 1 participating in this activity. The material presented consisted of the definition of financial literacy, factors, impacts, financial management strategies, as well as case studies or real examples of financial literacy. The results of this activity indicate that there is an increase in students’ understanding in learning financial literacy material, marked by students’ enthusiasm to listen and focus on the material presented. Not to mention, there were quite positive results from this activity: the students became more active in learning, as evidenced by the way they answered the questions I posed. This activity had a very positive impact on the younger generation, fostering awareness of the importance of financial literacy for their future.